An RCT of atraumatic restorative treatment for older adults: 5 year results. (April 2019) - da Mata, C; McKenna, G; Anweigi, L; Hayes, M; Cronin, M; Woods, N.; O'Mahony, D.; Allen, PF
Abstract: Objectives: to compare the survival of ART and a conventional restorative technique (CT) for restoring carious lesions in older adults after 5 years. Methods: In this parallel randomised controlled clinical trial, 219 independently-living adults were recruited from a dental hospital/community and a geriatric day hospital. Ninety-nine patients who met the inclusion criteria and presented with carious lesions were randomly allocated to receive either ART or conventional restorations (anaesthesia, rotary instruments and resin-modified glass ionomer). The status of restorations was assessed 6 months, 1, 2 and 5 years after restoration placement. Estimates of cumulative survival were calculated for each interval between assessments and a Cox Proportional Hazards (PH) model was fitted to the interval-censored survival time. Results: Three hundred restorations (ART n=142; CT n=158) were placed on 99 patients, 46 males and 53 females, with a mean age of 73.2, SD: 6.8 (65–90 yrs). After 5 years, ART and CT presented cumulative probability of survival of 85% and 79% (p=0.8095), respectively. Conclusions: ART presents survival rates comparable to a conventional technique, when treating older adults after 5 years. The ART approach could be a useful tool to provide dental care for older adults particularly in the nonclinical setting. (Trial Registration number: ISRCTN 76299321). Clinical Relevance: This study shows that ART presents survival rates comparable to conventional techniques to treat carious lesions in older patients after 5 years. It is well accepted by this age cohort, and therefore could be an alternative to treat the elderly, especially those who are homebound or cannot attend the dentist.